SIRT3 deficiency-induced mitochondrial dysfunction and inflammasome formation in the brain. Issue 1 (December 2018) - Tyagi, Alpna; Nguyen, Christy; Chong, Thomas; Michel, Cole; Fritz, Kristofer; Reisdorph, Nichole; Knaub, Leslie; Reusch, Jane; Pugazhenthi, Subbiah
Abstract SIRT3, the primary mitochondrial deacetylase, plays a significant role in enhancing the function of mitochondrial proteins. Downregulation of SIRT3 is a key component of metabolic syndrome, a precondition for obesity, diabetes and cardiovascular diseases. In this study, we examined the effects of brain mitochondrial protein hyperacetylation in western diet-fed Sirt3−/− mice, a model for metabolic syndrome. Brain mitochondrial proteins were hyperacetylated, following western diet feeding and Sirt3 deletion. To identity these hyperacetylated proteins, we performed a comprehensive acetylome analysis by label-free tandem mass spectrometry. Gene ontology pathway analysis revealed Sirt3 deletion-mediated downregulation of enzymes in several metabolic pathways, including fatty acid oxidation and tricarboxylic acid cycle. Mitochondrial respiration was impaired at multiple states, along with lower levels of mitochondrial fission proteins Mfn1 and Mfn2. Cleavage of procaspase-1 suggested inflammasome formation. Assembly of inflammasomes with caspase-1 and NLRP3 was detected as shown by proximity ligation assay. Markers of neuroinflammation including microgliosis and elevated brain IL-1β expression were also observed. Importantly, these findings were further exacerbated in Sirt3−/− mice when fed a calorie-rich western diet. The observations of this study suggest that SIRT3 deficiency-induced brain mitochondrial dysfunction and neuroinflammation in metabolic syndrome may play a role in late-life cognitive decline.